2006
DOI: 10.1521/jscp.2006.25.5.473
|View full text |Cite
|
Sign up to set email alerts
|

Self–Structure and Childhood Maltreatment: Successful Compartmentalization and the Struggle of Integration

Abstract: This study examined the self-structure (compartmentalization, self-complexity, and differential importance) of college students who reported maltreatment events before age 15. The focus was on emotional and sexual maltreatment, although physical maltreatment was taken into account. Only individuals who reported high sexual and high emotional events displayed the integrative self-structures expected of individuals with chronically salient negative self-aspects. Individuals who reported only sexual maltreatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 79 publications
3
27
1
Order By: Relevance
“…A study with non-clinical individuals suggests that individuals who reported a history of sexual abuse before the age of 15 had higher levels of compartmentalization than individuals with few (or no) abuse events (Showers, Zeigler-Hill, & Limke, 2006). However, in this study, borderline personality traits (assessed with the Borderline Features Scale of the Personality Assessment Inventory, Morey, 1991) were not associated with a more compartmentalized self-concept structure.…”
Section: Showers' Model Of Self-concept Organizationcontrasting
confidence: 77%
See 1 more Smart Citation
“…A study with non-clinical individuals suggests that individuals who reported a history of sexual abuse before the age of 15 had higher levels of compartmentalization than individuals with few (or no) abuse events (Showers, Zeigler-Hill, & Limke, 2006). However, in this study, borderline personality traits (assessed with the Borderline Features Scale of the Personality Assessment Inventory, Morey, 1991) were not associated with a more compartmentalized self-concept structure.…”
Section: Showers' Model Of Self-concept Organizationcontrasting
confidence: 77%
“…Thus, we hypothesize that patients with BPD exhibit more compartmentalized self-concepts than non-clinical individuals. Although one finding with nonclinical students appears to suggest that borderline personality features are unrelated to compartmentalization (Showers et al, 2006), findings from studies using non-clinical samples might not be an appropriate proxy for a clinical sample of patients diagnosed with BPD (Schechter, Strasser, Santangelo, Kim, & Edicott, 1994). For instance, BPD patients may differ from non-clinical controls on both quantitative and qualitative levels.…”
Section: Aims and Hypotheses Of The Present Studymentioning
confidence: 98%
“…before age 15 (Young-Wolff et al, 2011b). This operationalization of childhood maltreatment (i.e., combining physical abuse, sexual abuse, and neglect) is commonly used in maltreatment research (e.g., Topitzes et al, 2009;Zielinski, 2009), and the age cutoff of 15 years is consistent with many prior investigations of childhood maltreatment (e.g., Dervic et al, 2006;Gibb et al, 2001;Showers et al, 2006).…”
Section: Methodsmentioning
confidence: 66%
“…Showers & Zeigler-Hill, in press;Showers, Zeigler-Hill, & Limke, 2006). The present studies have 1-to 2-week time frames and so they treat evaluative organization at Time 1 as a predictor without assuming that this structure is stable.…”
Section: Self-structure: Evaluative Compartmentalization and Integrationmentioning
confidence: 98%